THE PITFALL OF RELYING ON A SPHYGMOMANOMETER DURING A HYPERTENSIVE CRISIS - Tan, Toh Leong; Ding, Chuan Hun (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Hypertensive crises can be life-threatening if undiagnosed due to the risk of acute target organ damage. This is a case of a middle-aged woman with poorly controlled hypertension who presented with a 3-day history of dyspnea, orthopnea, and cough productive of frothy sputum. Repeated attempts to measure her blood pressure (BP) using both a mercury and an electronic sphygmomanometer were unsuccessful. However, when an arterial catheterization of the right radial artery was performed, her mean BP was 358/151 mm Hg. A chest X-ray revealed cardiomegaly with plethoric lung fields. Following a diagnosis of hypertensive emergency with acute pulmonary edema, a glyceryl trinitrate infusion at a dose of 20 mg/min was commenced and titrated in an escalating manner. She was also given a single dose of intravenous frusemide 40 mg. Her BP was successfully reduced by 25% within 3 h of presentation.